OneFeather Mobile Wallet: A Digital Solution for Indigenous Peoples in Canada?*. (29th July 2021) - Lo, Kin; Liu, Fiana; Huang, Johnson
ABSTRACT: OneFeather is a real company located in British Columbia. The company aims to provide much‐needed services to Indigenous peoples, specifically those in Canada. This case involves a proposed digital wallet specifically designed for the needs of Indigenous peoples in Canada. Students are tasked to consider how the digital wallet needs to consider the unique circumstances of Indigenous peoples, the applicable tax laws, the appropriate technological foundation for the product, and strategies to roll out the product and attract users. RÉSUMÉ: Portefeuille mobile OneFeather : une solution numérique pour les populations autochtones au Canada? OneFeather est une société réelle établie en Colombie‐Britannique qui vise à fournir des services dont ont grandement besoin les peuples autochtones, et plus particulièrement ceux du Canada. La présente étude de cas porte sur un portefeuille mobile conçu spécifiquement pour répondre aux besoins des personnes autochtones au Canada. Les étudiants doivent déterminer de quelle façon ce portefeuille doit tenir compte des circonstances uniques des populations autochtones, des lois fiscales applicables, de la base technologique appropriée du produit ainsi que des stratégies pour lancer le produit et attirer des utilisateurs.